2014
DOI: 10.2302/kjm.2013-0009-re
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Penetrating Injuries of the Head and Neck:Current Practice at a Level I Trauma Center in the United States

Abstract: Penetrating neck injuries are commonly related to stab wounds and gunshot wounds in the United States. The injuries are classified by penetration site in terms of the three anatomical zones of the neck. Based on this zonal classification system, penetrating injuries to the head and neck have traditionally been evaluated by conventional angiography and/or surgical exploration. In recent years, multidetector-row computed tomography (CT) angiography has significantly improved detectability of vascular injuries an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 25 publications
(107 reference statements)
0
61
0
2
Order By: Relevance
“…Gracias et al6) have recommended CT scanning as an accurate and rapid method for evaluating the trajectory of penetration and Saito et al12) have reported that CT angiography has high sensitivity and a negative predictive value for vascular injury. However, the artifact generated by the foreign body on CT scan is a major obstacle when trying to determine if the surrounding structures are free from injury, as it was in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Gracias et al6) have recommended CT scanning as an accurate and rapid method for evaluating the trajectory of penetration and Saito et al12) have reported that CT angiography has high sensitivity and a negative predictive value for vascular injury. However, the artifact generated by the foreign body on CT scan is a major obstacle when trying to determine if the surrounding structures are free from injury, as it was in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Rating Comments RRL CTA neck with IV contrast 9 This procedure is the imaging study of choice. See references [2,5,6,8,[11][12][13][14][15][16][17].…”
Section: Radiologic Proceduresmentioning
confidence: 99%
“…B Arteriography neck 5 This procedure is usually used as a follow up test/treatment to a CTA or MRA. See references [2,6,11,20,21].…”
Section: Us Neckmentioning
confidence: 99%
“…Fifty percent of all trauma-related deaths are attributed to traumatic brain injury with 35% of these injuries resulting from gunshot wounds to the head [1-2]. This accounts for approximately 20,000 injuries [3-4]. Patients with penetrating head trauma with retained projectiles develop intracranial abscesses as a common complication.…”
Section: Introductionmentioning
confidence: 99%